INTERACTIVE MULTIMEDIA NEEDS ANALYSIS ANDROID BASED ON LESSONS NATURAL SCIENCE PRIMARY SCHOOL - Hendra; Aunurrahman; Indri Astuti (Jurnal Scientia, 2022)
The general purpose of this research is to analyze the need to develop android-based interactive multimedia in natural science subjects in elementary schools. This research was conducted at the 08 Mas Bangun Public Elementary School, North Kayong Regency in the 2020/2021 academic year. Based on the initial observations made by the researcher, it can be suggested that most of the fifth grade students at the State Elementary School 8 Mas Bangun have the means to carry out online learning activities with smartphone devices. However, in the initial observations, it was found that the learning media used by most educators at the 8 Mas Bangun State Elementary School still used conventional learning media and minimal use of ICT technology, although most of the 8 Mas Bangun Public Elementary Schools were equipped with computer and internet facilities. Keywords: Needs analysis, interactive multimedia , Android.